Improved Computed Tomography Contrast Injection Rates Through Implantable Chest Power Ports. Issue 6 (November 2020) - Fielding, James C.; Wagner-Bartak, Nicolaus A.; Javadi, Sanaz; Morani, Ajaykumar C.; Ganeshan, Dhakshinamoorthy; Ibarra-Rovira, Juan J.; Liu, Xinming; Jensen, Corey T.
Abstract : Objective: The aim of this study was to optimize chest port contrast injections using stepwise improvements. Methods: Ex vivo injections were tested. Two hundred scans using power port injections were then evaluated. Results: The highest flow rate was achieved using a 19G access needle, larger diameter tubing, and warmed contrast. The mean injection rates in baseline and postimprovement groups were 2.7 ± 0.4 and 4.8 ± 0.4 mL/s, respectively ( P < .0001). Conclusion: Component optimization of the port apparatus can maximize contrast flow rates.